A comparative study of the changes in the quality of life among patients with homonymous hemianopia, monocular blindness, or binocular diplopia - Ji Woong Chang (PLoS ONE, 2025)
To investigate changes in health-related quality of life (HRQOL), patients with homonymous hemianopia due to unilateral brain damage, monocular blindness with a best-corrected visual acuity of 20/1000 or less, or binocular diplopia for at least 6 months were enrolled. The 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) was used to evaluate the changes in HRQOL before and after the onset of the causative disease within and between the three study groups. The patients were asked to recall their state before disease onset and record it as accurately as possible for each question of the NEI VFQ-25, as well as score their current status. Among 43 included patients, 20 had homonymous hemianopia, 13 had monocular blindness, and 10 had binocular diplopia. The mean patient age was 56 years, and 12 patients were women (28%). A significant decrease in all HRQOL subscale scores was observed in the homonymous hemianopia and monocular blindness groups. In the binocular diplopia group, a lower number of subscales showed decreases in HRQOL. However, the changes in HRQOL before and after disease onset did not differ between groups. In conclusion, HRQOL change before and after homonymous hemianopia and monocular blindness did not differ. Considering the development background of the NEI VFQ-25, this questionnaire may not be sufficiently sensitive to distinguish HRQOL changes between the two disease groups. Hence, the NEI VFQ-25 might be useful for comparing HRQOL changes before and after the onset of a specific disease or before and after treatment, while not being sensitive to differentiate HRQOL differences between diseases. Thus, caution is needed when using the NEI VFQ-25 to compare HRQOL differences between disease groups.